AS VARIANTES PARA A CONSOANTE LATERAL ALVEOLAR E OS RÓTICOS EM CODA SILÁBICA NA FALA DO OESTE DO PARANÁ - Silva, Maria Siliane de Andrade Carpes Palhano da (2022)
In this dissertation we present the description of the variants for the alveolar lateral consonant and the rhotics in syllabic coda in the speech of the West of Paraná (BUSSE, 2010). Language, in its social dimension, reflects changes in time and space, arising from social, cultural and historical relationships. The western region of Paraná registers a linguistic polymorphism resulting from the colonization process, linguistic contacts and geographic location, in a border area, in view of these considerations, we delimit the research question: what are the variants for the alveolar consonant and the rhotics in syllabic coda, described by Busse (2010), in the speech of western Paraná, which may reveal the formation of linguistic areas in the region? This master's research is justified by the contribution to the portrait of the speech of Paraná, in the description of the variation and the linguistic change for the alveolar lateral and the rhotics in syllabic coda. The theoretical-methodological principles of this research are based on Dialectology and Geolinguistics, the general objective of this study is to analyze the variants for the alveolar lateral in syllabic coda and the variants for the rhotics in syllabic coda, in data collected by Busse (2010).The theoretical discussions that support the data analysis are based on: Lindau (1985), Ferreira e Cardoso (1994), Bisol (1996), Miranda (1996), Câmara Jr (1997), Coseriu (1998), Bagno (1999), Thun (2005), Oliveira (2006), Sá (2007), Labov (2008), Hora (2009), Cristófaro-Silva (2009), Tarallo (2011), Mollica (2015) and Galli (2016). Based on the data for the lateral consonant and the rhotics in syllabic coda described by Busse (2010) in the speech of the West of Paraná, the hypothesis of this collection, taking into account factors that contributed to the settlement process and the presence of southern settlers, thus indicating contexts that favor or inhibit the recording of variants for the lateral alveolar consonant, velarized, in syllabic coda, and of the tepe and multiple vibrating in syllabic coda. In short, in view of the data collected, we found that in the speech of the informants there is use of the variants presented, since the contact with different cultures contributes to a different speech.